The influence of participation and perceived system knowledge on perceived performance appraisal fairness - Kartikadewi, Apriliandhika; Purnomo, Ratno; Indiyastuti, Devani Laksmi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2018)
Accurate, accepted, and fair performance appraisals are critical to the organization. The main issues in the assessment of individual performance are with respect to the accuracy of measurement and fairness of assessment results. Previous research that has been done by some researcher shows the influence of performance appraisal process to justice result. The purpose of this study is to examine the influence of antecedent factors of fairness of performance appraisal consisting of participation and perceived system knowledge. The research design using questionnaires was used to collect data in public organizations (N = 75). The test results with multiple regression indicate that participation (two-way communication and involvement) and perceived system knowledge have a significant effect on the fairness of performance appraisal.